The complex motor sprint start performance as a double constraint management - Natta, F.; Boisnoir, A.; Cholet, D. (Sport Science Review, 2012)
In this study, the sprint start was investigated as a double constraint management: straightening 8 up from the ground to sprint forward. This management was explored using three separate groups of expertise defined according to individual sprint performance over 100 m (expert, intermediate and non sprinter). Two experimental conditions were studied according to the position in the starting-blocks: a spontaneous condition (S) and a forward perturbed condition (P) which aimed to carry the body weight more on the arms. In S condition, the statistical analyses showed that subjects were split into three classes according to the similarity of the data. These classes were not totally similar to the original groups of differing expertise. Class 1S subjects presented an efficient motor organization in which initial posture, straightening up and velocity were linked. In P condition, the sprinters were only split into two classes and sprint start efficiency was degraded. Nevertheless, the class 1P was perfectly superimposed on the expert group and presented a more homogenous response than that observed in class 1S. The motor synergies of the intermediate level could not be stabilized. This group and the non sprinter group belonged to the same class due to the similarity of their motor structure as the result of the perturbation.